PROBLEMATIKA LEARNING LOSS DI SDN TAKEN AKEN KECAMATAN JANAPRIA - Nurhariansyah Astari; Dewi Ratu Wahyuni; Mujaranah; Halimatus Sa'diyah; Basilius Redan Werang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Educational quality is a crucial factor in improving the quality of human resources and enhancing national competitiveness. Achieving quality education requires well-planned, systematic, and sustainable quality management strategies at both school and higher education levels. This study aimpentis to analyze quality management strategies implemented in educational institutions and identify the supporting and inhibiting factors affecting their implementation in improving educational quality. The study employed a library research method using a descriptive qualitative approach. Data were collected through an extensive review of scientific journal articles, books, educational regulations, and policy documents related to educational quality management. The findings indicate that effective quality management strategies include visionary leadership, continuous professional development of teachers and educational staff, the implementation of the Internal Quality Assurance System (SPMI), ongoing evaluation and continuous improvement, the integration of information technology, and active stakeholder participation. These strategies contribute to improved learning quality, institutional governance, student satisfaction, and graduate competitiveness. However, quality management implementation continues to face several challenges, including limited resources, disparities in educational quality across regions, weak quality culture, and the need to adapt to rapid technological advancements. Therefore, strong commitment and collaboration among all stakeholders are essential to fostering a culture of quality focused on continuous improvement, thereby ensuring sustainable enhancement of educational quality.